Effect of iron and zinc on flowering and postharvest life in gladiolus (Gladiolus spp.) - SINGH, ANIL K; HEMBROM, RAIMANI; SISODIA, ANJANA; PAL, A K; ASMITA, ASMITA (The Indian Journal of Agricultural Sciences, 2016)
An experiment was conducted at Banaras Hindu University in the year 2013-14 to find out the effect of foliar application of iron and zinc on flowering and postharvest life in gladiolus (Gladiolus spp.). Foliar application of ZnSO4 0.4% was found to be most effective for enhanced length of rachis (56.89 cm) and duration of flowering (15.33 days). While, days to opening of first floret was earliest with the treatment FeSO4 0.2% (81.25 days) and was significant to the other treatments. Maximum diameter of third floret (12.40 cm) was recorded with FeSO4 0.4% + ZnSO4 0.2% which was statistically at par with the treatment FeSO4 0.4%, FeSO4 0.2% and FeSO4 0.2% + ZnSO4 0.2%. Among postharvest indices, foliar application of FeSO4 0.4% prolonged the days to opening of the first floret (3.33 days) followed by FeSO4 0.2% and ZnSO4 0.2%. Whereas, days to opening of the third floret was maximum (5.67 days) with the treatment combination FeSO4 0.4% + ZnSO4 0.4% followed by FeSO4 0.4%. Maximum diameter of the first, third and fifth floret was recorded with the treatment combination FeSO4 0.2% + ZnSO4 0.2% which was statistically at par with ZnSO4 0.2%. Solution uptake was recorded maximum (130.00 ml) with the treatment FeSO4 0.2% followed by FeSO4 0.2% + ZnSO4 0.4%. Maximum vase-life was observed with the treatment ZnSO4 0.4% (15.67 days) followed by FeSO4 0.2% + ZnSO4 0.4% whereas; minimum vase life was recorded with the control(12.33 days).